Analisis Tarif Angkutan Feeder LRT Musi Emas Berdasarkan Pendekatan Biaya Operasional Kendaraan (BOK) - Zia Felina; Andriani Effendi (LPPM Universitas Abdurrab, 2026)
Effective public transportation services are one strategy to reduce public dependence on private vehicles and support urban transportation integration. One implementation is the Musi Emas LRT feeder transportation in Palembang City, which operates through a Buy-The-Service (BTS) scheme. This study aims to analyze the operational characteristics, Operational cost (BOK), and fare levels of the Musi Emas LRT feeder transportation on the Talang Kelapa–Talang Buruk and Asrama Haji–Sematang Borang corridors based on the BOK The study used a quantitative approach through field surveys, interviews, and questionnaires distributed to 400 respondents. The BOK analysis was conducted based on the Decree of the Director General of Land Transportation No. KP.792/AJ.205/DRJD/2021. The results show that the total BOK for both corridors reaches IDR 13,039,665,062 per year. The Operational cost fare is IDR 11,459 per passenger on the Talang Kelapa–Talang Buruk corridor and IDR 20,738 per passenger on the Asrama Haji–Sematang Borang corridor. The significant difference between BOK rates and user capabilities demonstrates the importance of government subsidies in the sustainability of BTS as well as tariff setting that takes into account the balance between operator and user interests